EML webinar overview: Origami-based metamaterials. (January 2022) - Jiang, Hanqing
Abstract: Recently, origami (ancient arts of paper folding) is becoming a popular tool to design mechanical metamaterials. This overview summarizes an EML webinar on Nov. 4th, 2021. It covers some demonstrations of rigid origami-based foldable electronics, kirigami (i.e., paper cutting) based stretchable electronics, microscale origami, and deformable origami-based mechanical metamaterials. The author hopes that this overview and the EML webinar (https://imechanica.org/node/25538 ) may provide new opportunities to the mechanics community to future explore the interesting properties of origami-based mechanical metamaterials with unique functionalities. EML Webinar speakers and videos are updated at https://imechanica.org/node/24098 .